Considering the Role of Ion Transport in Diffuson‐Dominated Thermal Conductivity. Issue 22 (27th April 2022) - Bernges, Tim; Hanus, Riley; Wankmiller, Bjoern; Imasato, Kazuki; Lin, Siqi; Ghidiu, Michael; Gerlitz, Marius; Peterlechner, Martin; Graham, Samuel; Hautier, Geoffroy; Pei, Yanzhong; Hansen, Michael Ryan; et al.
Abstract: Next‐generation thermal management requires the development of low lattice thermal conductivity materials, as observed in ionic conductors. For example, thermoelectric efficiency is increased when thermal conductivity is decreased. Detrimentally, high ionic conductivity leads to thermoelectric device degradation. Battery safety and design also require an understanding of thermal transport in ionic conductors. Ion mobility, structural complexity, and anharmonicity have been used to explain the thermal transport properties of ionic conductors. However, thermal and ionic transport are rarely discussed in direct comparison. Herein, the ionic conductivity of Ag + argyrodites is found to change by orders of magnitude without altering the thermal conductivity. Thermal conductivity measurements and two‐channel lattice dynamics modeling reveal that the majority of Ag + vibrations have a non‐propagating diffuson‐like character, similar to amorphous materials. It is found that high ionic mobility is not a requirement for diffuson‐mediated transport. Instead, the same bonding and structural traits that can lead to fast ionic conduction also lead to diffuson‐mediated transport. Bridging the fields of solid‐state ionics and thermal transport, it is proposed that a vibrational perspective can lead to new design strategies for functional ionic conducting materials. As a first step, the authors relate the so‐called Meyer–Neldel behavior in ionic conductors to phonon occupations. Abstract : Diffuson‐mediated thermal transport is revealed in ion conducting Ag + argyrodites by thermal transport measurements in conjunction with lattice dynamical modeling. The concurrent characterization of ionic transport shows that the magnitudes of both transport processes are not related on a macroscopic scale. Phonon occupation considerations suggest a shared microscopic origin, leading to new insights for ion conduction research.